Bentang Tubuh Putu Sutawijaya - Kris Budiman (Jurnal Kajian Seni, 2016)
My friendship with Putu Sutawijaya (PS) has lasted for the last seven years. HoweverI have known of his works and activities from mass media reportations and personalconversations with friends from many years before. PS has worked as an artist sincethe mid 1990s. His attitude and stance frequently show a sense of ambiguity, and eventension: on one side he shows a critical and distanced attitude and perspective, while onanother side he also emphasizes a certain fi delity upon the matter. Through this essayI plan to trace the milestones of PS’s works as an artifactual biography throughout thelast period of nearly fi fteen years. In this essay, I do not plan to assemble a periodizationdiagram of PS’s career as an artist, but rather I want to review the patterns or conventionsand general tendencies in his works.